Silver nanoparticles reduce brain inflammation and related neurotoxicity through induction of H2S-synthesizing enzymes - Gonzalez-Carter, D.A.; Leo, B.F.; Ruenraroengsak, P.; Chen, S.; Goode, A.E.; Theodorou, I.G.; Chung, K.F.; Carzaniga, R.; Shaffer, M.S.P.; Dexter, D.T.; Ryan, M.P.; Porter, A.E. (Nature Publishing Group, 2017)
Silver nanoparticles (AgNP) are known to penetrate into the brain and cause neuronal death. However, there is a paucity in studies examining the effect of AgNP on the resident immune cells of the brain, microglia. Given microglia are implicated in neurodegenerative disorders such as Parkinson's disease (PD), it is important to examine how AgNPs affect microglial inflammation to fully assess AgNP neurotoxicity. In addition, understanding AgNP processing by microglia will allow better prediction of their long term bioreactivity. In the present study, the in vitro uptake and intracellular transformation of citrate-capped AgNPs by microglia, as well as their effects on microglial inflammation and related neurotoxicity were examined. Analytical microscopy demonstrated internalization and dissolution of AgNPs within microglia and formation of non-reactive silver sulphide (Ag2S) on the surface of AgNPs. Furthermore, AgNP-treatment up-regulated microglial expression of the hydrogen sulphide (H2S)-synthesizing enzyme cystathionine-3-lyase (CSE). In addition, AgNPs showed significant anti-inflammatory effects, reducing lipopolysaccharide (LPS)-stimulated ROS, nitric oxide and TNFα production, which translated into reduced microglial toxicity towards dopaminergic neurons. Hence, the present results indicate that intracellular Ag2S formation, resulting from CSE-mediated H2S production in microglia, sequesters Ag+ ions released from AgNPs, significantly limiting their toxicity, concomitantly reducing microglial inflammation and related neurotoxicity.